Experimental infection of commercial layers using a Salmonella enterica serovar Gallinarum strain: Leukogram and serum acute-phase protein concentrations - Garcia, K. O. (2010)
The aim of the present study was to evaluate white blood cell counts and serum protein profiles of commercial layers experimentally infected with Salmonella Gallinarum (SG) in order to better understand the pathophysiology of the disease caused by this bacterium. 180 five-day-old commercial layers were divided into 3 groups (G); G1 and G2 received 0.2 mL of inoculate containing 3.3x10 8 CFU or 3.3×10 5 CFU SG resistant to nalidix acid (Nal r)/mL, respectively, directly into their crops. G3 group did not receive the inoculum. Birds were sacrificed 24 hours before (T1) and 24 hours after the infection (T2), and three (T3), five (T4), seven (T5), and ten (T6) days after the administration of the inoculum. White blood cell counts were carried out in a Neubauer hemocytometer and in blood smears. Serum protein concentrations, including acute-phase proteins, were determined using sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). Data were submitted to analysis of variance, and means were compared by Tukey's test (P <0.05). G1 and G2 groups presented higher leukocyte counts on T4 and T5, respectively, due to the increase of circulating lymphocytes and heterophils, with a significant difference relative to G3. In electrophoresis, an increase in the serum levels of ceruloplasmin, haptoglobin, and hemopexin and a decrease in transferrin, which are acute-phase proteins, was verified. IgA serum levels did not change; however, IgG concentration increased during the infection. In conclusion, the results provide information for the better understanding of the pathophysiology of fowl typhoid.